Influence of Technology Readiness and Flow Theory toward the Acceptance of Augmented Reality among Students in Private University in Jakarta, Indonesia - Budi, Arifitama; T.K.A, Rahman
Augmented Reality has recently gained popularity in the sphere of education. Unfortunately, most augmented reality research in private university in Indonesia is focused solely on software development. This will affect how ready and willing the student is to implement augmented reality. This research investigated the impact of readiness attitude and flow theory on augmented reality acceptance in a private university in Jakarta, Indonesia. This research was founded upon the Technology Acceptance Model and modified by adding the technology readiness index and flow to measure the influence of the readiness and the motivation among students’ acceptance of augmented reality technology. A quantitative methodology utilizing online questionnaire for data collection was designed to capture a wide range of responses efficiently, allowing for comprehensive analysis using SmartPLS3 by employing purposive sampling with 602 student respondents located in Jakarta. The results show that in terms of Technology Readiness, two variables, Innovativeness toward Perceived Usefulness (t = 5, p = 0) and Perceived Ease of Use (t = 3.613, p = 0) Insecurity toward Perceived Usefulness (t = 9.9, p = 0) and Perceived Ease of Use (t = 10.298, p = 0) ) are accepted and two variables Optimism toward Perceived Usefulness (t = 0.475, p = 0.635) and Perceived Ease of Use (t = 0.260, p = 0.795), Discomfort toward Perceived Usefulness (t = 0.050, p = 0.960) are rejected; In terms of Flow Theory and Technology Acceptance, all items were accepted. It is concluded that students are ready and accept augmented reality and showed no significant issues. However, there remains a lack of optimism among students regarding the feasibility of implementing AR and its benefits in classroom.